Mindful project management: resilient performance beyond the risk horizon - Kutsch, Elmar (PM World Journal, 2020)
Many authors treat projects with a strongly ‘mechanistic’ approach. The work can be broken down, executed and controlled as a series of interlocking parts. This is the technical, engineering-based conceptualisation, derived from the roots of the subject in large research and development projects. While acknowledging the many benefits of this view, we take a slightly different approach. We, in the book Mindful Project Management: Resilience Performance beyond the Risk Horizon, understand projects as ‘organic’ constructs, living and mindful entities existing for a finite period of time, consisting of people, supported by structures and processes. To continue the biological metaphor, this mindful organism is constantly challenged by environmental adversity. Success depends on remaining resilient, which we view as the ability to mindfully notice, interpret, prepare for, and consistently to contain and recover from such adversity.